The Upstarts Brad Stone PDF Uber, Airbnb, and the Battle for the New Silicon Valley - Brad Stone (Little, Brown and Company, 2017)
Ten years ago, the idea of getting into a stranger's car, or a walking into a stranger's home, would have seemed bizarre and dangerous, but today it's as common as ordering a book online. Uber and Airbnb have ushered in a new era: redefining neighborhoods, challenging the way governments regulate business, and changing the way we travel.